Monocular patching in subjects with right-hemisphere stroke affects perceptual-attentional bias - Barrett, Anna M; Burkholder, Stephanie (Journal of rehabilitation research and development, 2006)
Monocular patching is a possible inexpensive treatment for spatial neglect. Previous studies were unpromising, but since neglect symptoms are heterogeneous, fractionating spatial bias may detect significant effects of patching. Poststroke, perceptual-attentional (PA) spatial bias, motor-intentional (MI) spatial bias, or both may occur. In this study, six poststroke subjects bisected lines while self-monitoring their performance via a camera/video apparatus. We dissociated PA and MI spatial bias by right-left reversing visual feedback in some trials. Subjects were tested with and without right and left eye patches. Patching did not affect group line-bisection error, but both right and left patches decreased individual subject PA spatial bias (p < 0.05). We detected no patching effect on individual subject MI spatial bias (significant patch side by bias interaction, p = 0.03). When we examined each subject's results separately, patching improved performance in subjects who had greater PA and MI spatial biases. We conclude that monocular patching may primarily affect poststroke PA spatial bias. Further studies on this intervention are needed.